Longitudinal Task-Related Functional Connectivity Changes Predict Reading Development - Smith, Gregory J.; Booth, James R.; McNorgan, Chris (Frontiers in Psychology, 2018)
Longitudinal studies suggest developmentally dependent changes in lexical processing during reading development, implying a change in inter-regional functional connectivity over this period. The current study used functional magnetic resonance imaging (fMRI) to explore developmental changes in functional connectivity across multiple runs of a rhyming judgment task in young readers (8-14 years) over an average 2.5-year span. Changes in functional segregation are correlated with and predict changes in the skill with which typically-developing children learn to apply the alphabetic principle, as measured by pseudoword decoding. This indicates a developmental shift in the proportion of specialized functional clusters is associated with changes in reading skill and suggests a dependency of reading development on changes of particular neural pathways, specifically decreases in transitivity is indicative of greater network integration. This work provides evidence that characteristics of these pathways, quantified using graph-theoretic metrics, can be used to predict individual differences in reading development.